(untitled) (REMUNOM, 2026)
This study analyzes the contemporary tensions that permeate teacher training in Brazil, situated between emancipatory perspectives on education and technification processes resulting from current educational policies. The study is based on a critical-analytical theoretical essay, grounded in authors from the critical tradition of education and social philosophy, with special attention to the contributions of Adorno, Saviani, Imbernón, and Severino. The objects of analysis are the National Common Core Curriculum (BNCC) and Resolution CNE/CP nº 2/2019, documents that guide initial teacher training and express a normative rationality centered on the development of competencies and skills aligned with market demands. It is argued that such guidelines tend to promote the standardization of training processes, the emptying of the theoretical-critical dimension of teaching, and the reduction of teachers’ professional autonomy. The analysis shows that the centrality attributed to the technification of teacher training contradicts the principles of inclusive, democratic, and socially referenced education. It is concluded that the initial and continuing training of teachers needs to be redefined from an emancipatory perspective, capable of strengthening teaching as an intellectual, political, and transformative practice, committed to cultural plurality and educational inclusion.